Clinico-Epidemiological Profile and Outcome of Poisonous Snake Bites in Children using the WHO Treatment Protocol in Western Nepal (Journal of Nobel Medical College, 2015)
Background: Snake bite among children is an important public health problem in many tropical and subtropical countries. Limited studies are found on snake-bite in Nepal using the WHO snake-bite management guidelines. This study assessed the clinico-epidemiological profile and their outcome in snake-bite among children using the WHO Guidelines for treatment of snake bite.Methods: This is a descriptive study among 75 children less than 14 years of age admitted in Emergency Room (ER) of Lumbini Zonal Hospital from 2011-2012 with the history of poisonous snake bite.Results: More than half (56%) of the cases were males and 3/5th (58%) were above 10 years of age. About 40% of the patients were brought to ER within 6-12 hrs of snake bite. Common site of snake-bite was lower limbs (32%) followed by upper limbs (29%). Abdominal Pain (44%) was observed as most common sign/symptom of snake-bite poisoning after local pain followed by ptosis (17.3%). The case fatality rate (CFR) was 16.0%.Conclusion: Use of WHO treatment guideline for snakebite case management among children showed low CFR. However further studies need to done to compare the treatment outcomes between WHO guideline and the National Guidelines among snakebite cases among children. Journal of Nobel College of Medicine Vol.4(1) 2015: 21-25